Feminismo, sufragismo y mujeres en los partidos políticos en la Argentina de la primera mitad del siglo XX - Adriana María Valobra (Amnis)
The aim of this study is to analyze the path of the argentine’s suffragist through the first half of the twentieth century. We will highlight their militancy spaces and the modifications within them considering the changes that the peronist government introduced on the political mobilization of women after the sanction of the law of women's political rights in 1946.